2007
DOI: 10.1016/j.biopsych.2006.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of Neural Activation Associated with Ethanol Seeking: Effects of Naltrexone

Abstract: Background-Alcoholism, like other substance abuse disorders, is a chronically relapsing condition. Compared with other abused drugs, however, little is known about the neural mechanisms mediating ethanol (EtOH)-craving and -seeking behavior leading to relapse. This study, therefore, was conducted to identify candidate brain regions that are recruited by an EtOH-associated contextual stimulus (S + ). A secondary objective was to determine whether EtOH S + -elicited neural recruitment patterns are modified by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
133
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(149 citation statements)
references
References 95 publications
11
133
2
1
Order By: Relevance
“…It has been shown that cocaine-and alcohol-paired discrete cues did not activate c-Fos expression in the CeA (Neisewander et al, 2000;Ciccocioppo et al, 2001;Dayas et al, 2007;Zhao et al, 2006). However, in the latter studies many extinction sessions were run prior to the final reinstatement session (a factor which could account for the discrepancies between the results of those studies and our data).…”
Section: Pattern Of C-fos Activation In the Amygdala: A Role In Plastcontrasting
confidence: 84%
“…It has been shown that cocaine-and alcohol-paired discrete cues did not activate c-Fos expression in the CeA (Neisewander et al, 2000;Ciccocioppo et al, 2001;Dayas et al, 2007;Zhao et al, 2006). However, in the latter studies many extinction sessions were run prior to the final reinstatement session (a factor which could account for the discrepancies between the results of those studies and our data).…”
Section: Pattern Of C-fos Activation In the Amygdala: A Role In Plastcontrasting
confidence: 84%
“…For example, in a ethanol reinstatement model using a discriminative stimulus task, increased Fos expression was observed in the Acb (Dayas et al, 2007), in addition to the Acb, BLA, and CE in a separate study (Zhao et al, 2006). Furthermore, recent findings from an ethanol cue-induced reinstatement study found increases in BLA and CE activation in response to a discrete cue (Radwanska et al, 2007).…”
Section: Lesions Of the Acbc Facilitate Loss Of Respondingmentioning
confidence: 95%
“…Such learning is important because it can alter physiological/behavioral responses, motivational states (e.g., craving), or expectancies that affect the probability, vigor, or cue-directed nature of ethanolseeking behavior (Krank, 1989(Krank, , 2003Cunningham, 1994Cunningham, , 1998Corbit and Janak, 2007). Pavlovian learning may be especially involved in triggering relapse to ethanol seeking after periods of abstinence or extinction (Krank and Wall, 1990;Katner and Weiss, 1999;Ciccocioppo et al, 2001Ciccocioppo et al, , 2002Ciccocioppo et al, , 2003Nie and Janak, 2003;Zironi et al, 2006;Dayas et al, 2007). Despite the prevalence of alcohol abuse and dependence, surprisingly little is known about the neural areas that mediate the acquisition and expression of ethanol-seeking behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a pivotal role of the hippocampus in conditioned responses to fearful stimuli and associative learning relevant for anxiety-related responses is well documented (Anagnostaras et al, 2001;LeDoux, 1992, 1994), the dorsal hippocampus (DH) is also known to have a role in contextual memory retrieval and the occasion-setting action of contextual stimuli (eg Holland and Bouton, 1999). Indeed, the DH has been implicated in the control of ethanol- (Dayas et al, 2007;Zhao et al, 2006) and cocaine-seeking (Franklin and Druhan, 2000;Fuchs et al, 2005;Neisewander et al, 2000) induced by contextual stimuli in reinstatement models. The subiculum, a related brain structure that receives the majority of hippocampal projections (Commins et al, 1998;Stewart, 1997;Witter and Groenewegen, 1990;Young et al, 1997), is hypothetized to participate in mediating associative learning and, thus, likely to play an important role in behavior controlled by environmental stimuli related to drugs of abuse.…”
Section: Introductionmentioning
confidence: 99%